2008
DOI: 10.1021/bm800502j
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Heat-Induced β-Lactoglobulin Aggregates and their Complexes with Sodium-Dodecyl Sulfate

Abstract: We report on the conformation of heat-induced bovine beta-lactoglobulin (betalg) aggregates prepared at different pH conditions, and their complexes with model anionic surfactants such as sodium dodecyl sulfate (SDS). The investigation was carried out by combining a wide range of techniques such as ultra small angle light scattering, static and dynamic light scattering, small angle neutron scattering, small-angle X-ray scattering, electrophoretic mobility, isothermal titration calorimetry (ITC) and transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
284
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 290 publications
(309 citation statements)
references
References 51 publications
19
284
0
Order By: Relevance
“…The powder was dialysed and freeze-dried before use, as described in literature 16 . A 2 wt% solution was prepared by dissolving the powder in Milli-Q water at room temperature over at least 1 h. The solution was centrifuged at 10,800g over a period of 1 h at 20 8C using a Sorvall RC3C Plus centrifuge (DuPont), adjusted to pH 2, and filtered through a 0.45-mm Millipore filter before heat treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The powder was dialysed and freeze-dried before use, as described in literature 16 . A 2 wt% solution was prepared by dissolving the powder in Milli-Q water at room temperature over at least 1 h. The solution was centrifuged at 10,800g over a period of 1 h at 20 8C using a Sorvall RC3C Plus centrifuge (DuPont), adjusted to pH 2, and filtered through a 0.45-mm Millipore filter before heat treatment.…”
Section: Methodsmentioning
confidence: 99%
“…b-Lactoglobulin has been particularly well studied, because it represents both a relevant model system and a major whey protein of interest to the food industry [14][15][16][17][18][19][20][21][22] .…”
mentioning
confidence: 99%
“…The solution had a polydispersity index (PI or PDI) of 0.707, corresponding to a polydispersity of 84% PD. PD vaues of <20% are often taken to imply the presence of single protein molecules whereas values > 20% indicate aggregation [47,48] Unchromatographed transferrin and monomeric rTf were too polydisperse to allow measurement of their particle sizes, showing a propensity for ongoing aggregation. DLS measurements are therefore consistent with a tendency towards higher order protein aggregation.…”
Section: Dynamic Light Scatteringmentioning
confidence: 99%
“…Risso et al (2000) for instance reported that the net charge of heated casein micelles resuspended in aqueous Tris-HCl-CaCl 2 buffer at pH 6.4 could be increased by the binding of anionic fluorescent probes. Jung et al (2008) further reported that the double-coating of β-LG heat-induced complexes by SDS in water through successive electrostatic and hydrophobic interactions could eventually reverse their net charge. However, application of the method to whey protein/κ-casein complexes may have consequences on their structure, especially in the case of surfactants, because they are partially built on hydrophobic interactions .…”
Section: Introductionmentioning
confidence: 97%